Runoff quality and pollution loadings from a tropical urban catchment - Yusop, Z.; Tan, L. W.; Ujang, Zaini; Mohamed, M.; Nasir, K. A. (International Water Association Publishing, 2005)
Runoff quality draining from 17.14 km2 urban catchment in Johor Bahru, Malaysia, was analysed. The land-use consists of residential (30.3%), agricultural (27.3%), open space (27.9%), industrial (8.1%) and commercial (6.4%) areas. Three storm events were sampled in detail. These storms produced stormflow between 0.84 mm and 27.82 mm, and peakflow from 2.19 m3/s to 42.36 m3/s. Water quality showed marked variation during storms especially for TSS, BOD and COD with maximum concentrations of 778 mg/l, 135 mg/l and 358 mg/l, respectively. Concentrations of TOC, DOC, NH3-N, Fe and level of colour were also high. In general, the river quality is badly polluted and falls in Class V based on the Malaysian Interim National Water Quality Standards. Event Mean Concentrations (EMC) for various parameters varied considerably between storms. The largest storm produced higher EMC for TSS, NO3-N and SS whereas the smaller storms tend to register higher EMC for BOD, COD, NH3-N, TOC, Ca, K, Mg, Fe and Zn. Such variations could be explained in terms of pollutant availability and the effects of flushing and dilution. Based on a three-month average recurrence interval (ARI) of rainfall, the estimated event loadings (ton/ha) of TSS, BOD, COD, TOC, NH3-N and NO3-N were 0.055, 0.016, 0.012, 0.039, 0.010, 0.0007 and 0.0002, respectively. Heavy metals present in trace quantities. Storms with 3 months ARI could capture about 70% of the total annual loads of major pollutants.